Design and development of an electronic system for the selective stimulation and simultaneous measurement of the skin impedance - Esser, Eduardo Mussoi (2011)
It has been found that electrical current applied to the human skin stimulates some of the peripheral nerves and fibers of the human body, causing several reactions such as the increase of sweat production. Moreover the analyses of such reactions can be used to diagnose some diseases, for example diabetes. Nevertheless, most of the electrical stimulation devices, which use mostly square wave signals, are not optimal since they stimulate not only the desired glands (C-fiber) but also the Aδ-fibers of the body, responsible for the fast pain sensation. In this context, this work presents the development of a microcontroller based electronic system for controlling the electrical stimulation of human skin. The objective of the system was to make it possible to test different patterns of electric current pulses, in order to obtain the ideal shape for maximizing the desired stimulation effects with minimal pain. The result of the project was an electronic device that generates electrical pulses based on pre-programmed signals, which are received through a USB interface from a PC. Moreover the system was able to measure the skin impedance value during the electrical stimulation, complementing the diagnosis. The results of the tests carried out with the system showed that the pain intensity during the stimulation could be minimized according to the pulse shape not changing the amplitude and energy of the signal. Moreover a slight difference in the skin impedance was observed when different shapes were applied.